When Confucius meets Erikson: An innovative life review program on Chinese seniors with probable dementia. (July 2021) - Lin, Li-Jung; Yen, Hsin-Yen
Before Erikson proposed the life stages, Confucius concluded an autobiographic review of his entire life in about 500 BC. Confucius' life stages may be closer to the life experiences of Chinese older adults. Therefore, the purpose of this study was to examine the effect of the life review program on cognitive ability, life satisfaction, meaning of life, and ego integrity. The experiment was based on a single-group time-series design with a four-time test across 21 weeks. The evoking materials were horticultural activities held in seven weekly sessions. The innovative life review program was in accordance with a combination of Confucius' and Erikson's life stages. Nine participants completed all sessions. There was a significant positive effect of time on participants' cognitive ability and meaning of life after the program. A combination of Confucius' and Erikson's life stages can be more advantageous for Chinese older adults than only Erikson's life stage.